2012
DOI: 10.4049/jimmunol.1200133
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Stimulates a “Feed-Forward” NF-κB–Driven Molecular Pathway That Regulates IFN-β Expression in Carcinoma Cells

Abstract: IFN-β and the CD40L (CD154) share important roles in the antiviral and antitumor immune responses. In this study, we show that CD40 receptor occupancy results in IFN-β upregulation through an unconventional “feed-forward” mechanism, which is orchestrated by canonical NF-κB and involves the sequential de novo synthesis of IFN regulatory factor (IRF)1 and Viperin (RSAD2), an IRF1 target. RelA (p65) NF-κB, IRF1, and Viperin-dependent IRF7 binding to the IFN-β promoter largely controls its activity. However, full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…NF-κB and IRF1 were activated in MΦ+RM1(HA) but not in MΦ+MC4(HA) cocultures. Both transcription factors activate inflammatory responses and in some contexts cooperate with the activation of proinflammatory cytokines (21,22). These findings correlate with the differential inflammatory response of macrophages in the cocultures with the apoptotic prostate cancer RM1 and the noncancer MC4 cells (Figure 1, A-C).…”
Section: Proinflammatory Cytokines Are Induced In Macrophages Upon Apsupporting
confidence: 64%
“…NF-κB and IRF1 were activated in MΦ+RM1(HA) but not in MΦ+MC4(HA) cocultures. Both transcription factors activate inflammatory responses and in some contexts cooperate with the activation of proinflammatory cytokines (21,22). These findings correlate with the differential inflammatory response of macrophages in the cocultures with the apoptotic prostate cancer RM1 and the noncancer MC4 cells (Figure 1, A-C).…”
Section: Proinflammatory Cytokines Are Induced In Macrophages Upon Apsupporting
confidence: 64%
“…Interestingly, Moschonas has indicated that stimulation of CD40 by its ligand has promoted the expression of IFN-β through the binding IRF7 to its promoter. IRF7 is a transcriptional factor which regulates the expression of type I interferon [48]. Silencing of IRF7 pathways in breast cancer accelerated bone metastasis through immune escape [49].…”
Section: Discussionmentioning
confidence: 99%
“…Non-canonical NFκB signaling is slow but persistent and requires de novo NIK protein synthesis and NIK stabilization [58]. It is activated by receptors that belong to the TNFR (tumor necrosis factor receptor) superfamily like BAFF (B-cell-activating factor), CD40 or lymphotoxin β-receptor (LTβR) [59][60][61][62].…”
Section: The Non-canonical Nfκb Signaling Pathwaymentioning
confidence: 99%